Selected Gender Gap Indicators – Comparison of V4 Countries within EU Context - Řezanková, Hana; Křečková, Zuzana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper examines similarities and distinctions of EU countries based on the Global Gender Gap Index and its four subindexes (Economic Participation and Opportunity, Educational Attainment, Health and Survival, Political Empowerment) reported in 2016. Multivariate statistical methods (cluster analysis and discriminant analysis) are applied for this purpose. Influence of individual subindexes on results of statistical analyses is discussed. The groups of countries are identified and models for country classification are proposed and compared. Changes in index values, as well as, relationships between selected gender and economic indicators (Global Competitiveness Index and GDP per capita) are investigated for period 2006 to 2016. Special attention is paid to the Visegrad Group countries within EU context
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 373-386
Keywords: gender gap indicators; multivariate statistical methods; EU countries